Analysis and Visualization of Global Research Trends in Sustainable Shrimp Farming Through Bibliometrics - Mochamad Ibnu Syina Noor; Yayat Ruhiat; Widya Ernayati K. (Industrial and Domestic Waste Management, 2026)
This study aimed to comprehensively examine global research trends in sustainable shrimp farming and identify research gaps that require further investigation. The analysis was based on 294 research articles published between 2014 and 2023 and indexed in the Scopus database. Using bibliometric methods and VOSviewer software, the study evaluated publication output, subject areas, journals, authors, keywords, countries, and other bibliometric indicators to assess the global development of research in this field over the study period. The field of sustainable shrimp farming expanded rapidly, with a continuous increase in the number of publications through 2023. India recorded the highest number of publications, with 47 articles. The most frequently occurring keywords included "Bacterium," "Carbon," "Crustacean," "Food Supplementation," "Immunity," "Microbiology," "Nonhuman," "Penaeus vannamei," "Probiotic," and "Vibrio." The bibliometric analysis provided valuable insights into the current status, research progress, and future potential of this field. Based on the findings, several promising directions for future research were identified: (1) the relationship between dietary supplementation and immune responses, including the interactions between probiotics and Vibrio; (2) the immune responses of shrimp species to Vibrio, carbon-related factors, and food supplementation; and (3) the influence of probiotics on the cultivation and health performance of Penaeus vannamei.